2000
DOI: 10.1046/j.1365-3083.2000.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subcutaneous Interleukin‐2 Therapy on Phenotype and Function of Peripheral Blood Mononuclear Cells in Human Immunodeficiency Virus Infected Patients

Abstract: In the context of clinical therapy with recombinant human interleukin‐2 (IL‐2), we monitored immunological alteration in 10 human immunodeficiency virus type‐1 (HIV‐1)‐infected individuals, on stable antiretroviral therapy, who had a CD4+ cell count between 200 and 500 cells/mm3. Subcutaneous IL‐2 was prescribed thrice weekly (at a dose of 3 × 106 IU) for 24 weeks and the patients were followed‐up for 32 weeks. IL‐2 treatment induced an increase in the CD4+ percentage (P < 0.001) and CD4+ cell count (P < 0.009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
3
6
1
Order By: Relevance
“…This finding is in accordance with those of several other studies [8,9,15]. However, we found that IL-2 treatment induced an impaired lymphocyte function expressed as a decreased proliferative response and decreased cytotoxic T cell (CTL) activity [16]. The purpose of this study was to investigate whether changed telomere lengths are associated with the previously observed depressed lymphocyte function.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in accordance with those of several other studies [8,9,15]. However, we found that IL-2 treatment induced an impaired lymphocyte function expressed as a decreased proliferative response and decreased cytotoxic T cell (CTL) activity [16]. The purpose of this study was to investigate whether changed telomere lengths are associated with the previously observed depressed lymphocyte function.…”
Section: Introductionsupporting
confidence: 92%
“…There were no changes in antiretroviral regimens 3 months prior to initiation of IL-2 treatment or throughout the study. Blood samples were collected 4 weeks before therapy, at enrolment, and 4, 8,12,16,20,24,28,32 and 36 weeks after enrolment. The Danish National Health Board and the local ethics committee approved the trial, and all patients provided their written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…First, lymphocyte proliferative response, LAK and CTL functions are known to decrease following subcutaneous low-dose IL-2 administration to HIV-infected individuals and NK activity, following an initial increase, decreased below baseline levels during treatment of these patients. 30 Second, impaired NK cell activity might adversely impact on the control of minimal residual disease in cancer patients. Thus, an additional finding of this study was that NK activity was not significantly depressed after low-dose IL-2 treatment at any time point.…”
Section: Discussionmentioning
confidence: 99%
“…A similar reduction in CD45RA ϩ T cell count has already been reported at late time points after subcutaneous low-dose IL-2 administration. 30 This phenomenon has no apparent explanation and suggests that, similar to myelopoietic growth factors, IL-2 given soon after PBSCT also produces long-lasting immune effects with persistent modulation (observable until day 100 post-PBSCT) in the number of de novo generated T cells (ie naive CD45RA ϩ T cells). The detrimental effect of IL-2 addition on CD45RA ϩ T cell regeneration is surprising and confirms the lack of favorable post-PBSCT immune effects by IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…(15) Major players have emerged, and immunotherapy aimed at manipulating these has already shown promise. (22)(23)(24) The current challenge is to master the art of navigating the fine line between protection and pathology in TB. (25,26) …”
mentioning
confidence: 99%